Positive interaction between prebiotics and thiazolidinedione treatment on adiposity in diet‐induced obese mice. (19th April 2014) - Alligier, Maud; Dewulf, Evelyne M.; Salazar, Nuria; Mairal, Aline; Neyrinck, Audrey M.; Cani, Patrice D.; Langin, Dominique; Delzenne, Nathalie M.
<x xml:space="preserve">Abstract</x> Objectives To investigate whether inulin‐type fructan (ITF) prebiotics could counteract the thiazolidinedione (TZD, PPARγ activator) induced‐fat mass gain, without affecting its beneficial effect on glucose homeostasis, in high‐fat (HF) diet fed mice. Methods Male C57bl6/J mice were fed a HF diet alone or supplemented with ITF prebiotics (0.2 g/day × mouse) or TZD (30 mg pioglitazone (PIO)/kg body weight × day) or both during 4 weeks. An insulin tolerance test was performed after 3 weeks of treatment. Results As expected, PIO improved glucose homeostasis and increased adiponectinaemia. Furthermore, it induced an over‐expression of several PPARγ target genes in white adipose tissues. ITF prebiotics modulated the PIO‐induced PPARγ activation in a tissue‐dependent manner. The co‐treatment with ITF prebiotics and PIO maintained the beneficial impact of TZD on glucose homeostasis and adiponectinaemia. Moreover, the combination of both treatments reduced fat mass accumulation, circulating lipids and hepatic triglyceride content, suggesting an overall improvement of metabolism. Finally, the co‐treatment favored induction of white‐to‐brown fat conversion in subcutaneous adipose tissue, thereby leading to the development of brite adipocytes that could increase the oxidative capacity of the tissue. Conclusions ITF prebiotics decrease adiposity and improve the metabolic response in HF fed mice treated with TZD.